2021
DOI: 10.1038/s41467-021-24220-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher CSF sTNFR1-related proteins associate with better prognosis in very early Alzheimer’s disease

Abstract: Neuroinflammation is associated with Alzheimer’s disease, but the application of cerebrospinal fluid measures of inflammatory proteins may be limited by overlapping pathways and relationships between them. In this work, we measure 15 cerebrospinal proteins related to microglial and T-cell functions, and show them to reproducibly form functionally-related groups within and across diagnostic categories in 382 participants from the Alzheimer’s Disease Neuro-imaging Initiative as well participants from two indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…In a different context, the involvement of mtDNA signaling in pathogenesis of Alzheimer's disease (AD) is also currently under discussion, as several reports of mitochondrial dysfunction and also the dysfunction of Pink1/Parkin, excessive ROS production are reported in association with AD (Witte et al, 2009;Ye et al, 2015). However, a direct contribution of mtDNA in pathogenesis of AD was not proven yet, the inflammatory component, showing induction of the inflammasome, cytokines and NF-ΚB might hint a correlation of mtDNA accumulation in AD (Heneka et al, 2013;Ahmed et al, 2017;Hu et al, 2021).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In a different context, the involvement of mtDNA signaling in pathogenesis of Alzheimer's disease (AD) is also currently under discussion, as several reports of mitochondrial dysfunction and also the dysfunction of Pink1/Parkin, excessive ROS production are reported in association with AD (Witte et al, 2009;Ye et al, 2015). However, a direct contribution of mtDNA in pathogenesis of AD was not proven yet, the inflammatory component, showing induction of the inflammasome, cytokines and NF-ΚB might hint a correlation of mtDNA accumulation in AD (Heneka et al, 2013;Ahmed et al, 2017;Hu et al, 2021).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Diniz et al found that a high serum sTNFR1 level was associated with a higher risk of progression from mild cognitive impairment (MCI) to AD [ 25 ]. Hu et al showed that higher levels of proteins related to sTNFR1 were associated with a reduced risk of conversion to dementia and that these sTNFR1-related inflammatory proteins provided prognostic information independent of established Alzheimer’s markers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble forms of the amyloid precursor protein sAPPα and sAPPβ were also measured in the Luminex 200 platform (Immuno-Biological Laboratories, Minneapolis, MN) due to their implication in ALS [23,24]. All assays were performed using manufacturers' protocols with the exception that 100 mL of CSF was used in the inflammatory protein assays, and these assays have been used extensively in the Hu Lab to characterize neurodegenerative, inflammatory, and other biological processes in aging, Alzheimer's disease (AD), multiple sclerosis (MS), HIV-associated neurocognitive dysfunctions, and COVID-19-related neurological dysfunctions with high accuracy and precision [22,[25][26][27][28].…”
Section: Methodsmentioning
confidence: 99%